Effects of AMF inoculation on the eco-physiological characteristics of Imperata cylindrica under differing soil nitrogen conditions - Jia, Tong; Zhang, Yue; Yao, Yushan; Wang, Yu; Liang, Xueli; Zheng, Mengyao; Zhao, Lijuan; Chai, Baofeng (Frontiers in Plant Science, 2023)
Arbuscular mycorrhizal fungi (AMF) play a key role in terrestrial ecosystems, while the ecological restoration application of AMF in mining areas has been progressively gaining attention. This study simulated a low nitrogen (N) environment in copper tailings mining soil to explore inoculative effects of four AMF species on the eco-physiological characteristics of Imperata cylindrica, and provided plant-microbial symbiote with excellent resistance to copper tailings. Results show that N, soil type, AMF species, and associated interactions significantly affected ammonium (NH4+), nitrate nitrogen (NO3-), and total nitrogen (TN) content and photosynthetic characteristics of I. cylindrica. Additionally, interactions between soil type and AMF species significantly affected the biomass, plant height, and tiller number of I. cylindrica. Rhizophagus irregularis and Glomus claroideun significantly increased TN and NH4+ content in the belowground components I. cylindrica in non-mineralized sand. Moreover, the inoculation of these two fungi species significantly increased belowground NH4+ content in mineralized sand. The net photosynthetic rate positively correlated to aboveground total carbon (TC) and TN content under the high N and non-mineralized sand treatment. Moreover, Glomus claroideun and Glomus etunicatum inoculation significantly increased both net photosynthetic and water utilization rates, while F. mosseae inoculation significantly increased the transpiration rate under the low N treatment. Additionally, aboveground total sulfur (TS) content positively correlated to the intercellular carbon dioxide (CO2) concentration, stomatal conductance, and the transpiration rate under the low N sand treatment. Furthermore, G. claroideun, G. etunicatum, and F. mosseae inoculation significantly increased aboveground NH4+ and belowground TC content of I. cylindrica, while G. etunicatum significantly increased belowground NH4+ content. Average membership function values of all physiological and ecological I. cylindrica indexes infected with AMF species were higher compared to the control group, while corresponding values of I. cylindrica inoculated with G. claroideun were highest overall. Finally, comprehensive evaluation coefficients were highest under both the low N and high N mineralized sand treatments. This study provides information on microbial resources and plant-microbe symbionts in a copper tailings area, while aiming to improve current nutrient-poor soil conditions and ecological restoration efficiency in copper tailings areas.